The relationship between preparation for gentle birth and the degree of anxiety of first pregnant women in facing labor at PMB Mutiara Medan Sunggal - Paninsari, Debora; Sandi, Hasnita Treesna; Agusdiana, Agusdiana; Graciela, Angel; Anggraini, Bunga; Hagana, Cerina Er (Priviet Social Sciences Journal, 2022)
Psychological changes make pregnant women experience anxiety in facing the delivery process, including the conditions that occur during the delivery process. To overcome this anxiety, the benefits of Gentle Birth are needed so that mothers can give birth in peace, free from fear and anxiety. Purpose: This study was to determine the relationship between preparation for gentle birth and the degree of anxiety of first pregnant women in facing labour. Method: the research used was a quantitative approach using a cross-sectional design which was carried out at PMB Mutiara Medan Sunggal in October 2022. The total population used as the research sample was 30 respondents using the total sampling technique. The data collection method uses a questionnaire with an ordinal scale. Results: 19 people (79,2%) did a good gentle birth preparation with low anxiety, 5 people (20,8%) had high anxiety. Meanwhile, there were 2 respondents (33,3%) who did not prepare for gentle birth with a low degree of anxiety, and 4 people (66,7%) with a high degree of anxiety. In the Statistical Test (Chi Square), a p-value of 0.090 is obtained, meaning that this value is < alpha (0.05). Thus it is concluded that H0 is rejected. Conclusion: That there is a relationship between preparation for gentle birth with the degree of anxiety of primigravida pregnant women at PMB Mutiara Medan Sunggal.